2000
DOI: 10.1111/j.1348-0421.2000.tb02542.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection and Intussusception: A View from Retrospect

Abstract: A live orally-administrable rhesus rotavirus (RRV) tetravalent (TV) vaccine, licensed in the U.S.A. and the European Union, was recalled from the market because it was suspected to increase the risk of intussusception during the week following immunization. In contrast, natural rotavirus infection is generally believed not to cause intussusception. Because my experience contributed to the first paper that linked intussusception with rotavirus infection, I have re-examined our own data published 22 years ago an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…12 Dr Nakagomi postulated that some strains, such as a G3 serotype, could induce intussusception whereas others may not. This finding might explain the yearly variation in the incidence of intussusception.…”
Section: Intussusception Pathogenesismentioning
confidence: 99%
“…12 Dr Nakagomi postulated that some strains, such as a G3 serotype, could induce intussusception whereas others may not. This finding might explain the yearly variation in the incidence of intussusception.…”
Section: Intussusception Pathogenesismentioning
confidence: 99%
“…It is a pediatric emergency in infants and shows a peak in occurrence in infants aged at 6-8 months with no apparent seasonality (1,2). This condition received much attention when a tetravalent rotavirus vaccine, RotaShield (Wyeth-Lederle Vaccines and Pediatrics) (3), was suspected to cause intussusception in approximately 1 in 10,000 vaccine recipients, resulting in the withdrawal of this vaccine from the market in the United States (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It is a pediatric emergency in infants and shows a peak in occurrence in infants aged at 6-8 months with no apparent seasonality (1,2). This condition received much attention when a tetravalent rotavirus vaccine, RotaShield (Wyeth-Lederle Vaccines and Pediatrics) (3), was suspected to cause intussusception in approximately 1 in 10,000 vaccine recipients, resulting in the withdrawal of this vaccine from the market in the United States (2,(4)(5)(6). Consequently, large, phase III clinical trials, each recruiting more than 60,000 infants were conducted, and their results showed that two succeeding rotavirus vaccines, Rotarix (GlaxoSmithKline Biologicals, Rixensart, Belgium) and RotaTeq (Merck & Co., Whitehouse Station, N.J., USA), were safe with respect to intussusception (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the electropherotype of intussusception causing rotaviruses, a hypothesis has been postulated that wild type G3 human rotaviruses may selectively cause intussusception in infants (19). Therefore, one might consider that intussusception is the particular complication of RRV or serotype G3 rotavirus.…”
Section: Discussionmentioning
confidence: 99%